Implementation of Public-Private Partnership in the Healthcare Management System - Natalia Ovcharova; Monika Grabowska (Health Economics and Management Review)
This article states that the private sector and the government can resolve contradictions and bridge interaction gaps through a public-private partnership due to complementing each other functionally. The study aims to determine the elements of public-private partnership development in healthcare and primary conditions for further forming an effective environment for implementing the principles of public-private partnership in healthcare management. This investigation examined the public-private partnership state worldwide and in Ukraine and the prospects for its development in the context of healthcare reform. It was noted that cooperation between the public and private sectors is becoming increasingly social. However, the current practice does not show effectiveness in achieving certain goals. The properties and differences in realizing social public-private partnership projects were investigated. The risks and problems in the implementation of public-private partnerships in healthcare were identified. The authors developed the structural and target model for ensuring the development of public-private partnerships in healthcare. It was determined that the basic conditions contributing to the successful implementation of public-private partnership projects in healthcare should include the factors as follows: political willpower to promote the development and support of public-private partnership; legislative and regulatory system to attract private sector funding; availability of feasible and effective projects and mechanisms for their selection; availability of information and staff needed for project implementation. The findings substantiated that state budget support is essential in reducing the risks of a private partner at the initial stage of public-private partnership development. The world experience showed that state funding of public-private partnership projects in healthcare might vary depending on the project life cycle stage. Given the importance of improving the funding of public-private partnerships, especially in terms of state budget funding for health projects, key elements and possible areas for improvement were identified.